Attitudes of individuals with chronic diseases towards members of ingroup and outgroup of healthy people - Smirnova, Yuliya S.; Zaitseva, Yuliya V. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The process of social categorization on the basis of health status and its negative consequences (prejudice, stigmatization, discrimination) are considered in the article. The importance of studying of stigmatized minorityʼs attitudes towards members of ingroup and outgroup is argued. The results of empirical research of attitudes towards healthy people and people with chronic diseases are presented. The attitudesʼ structure and content as well as the differences depending on the degree of obviousness, heaviness and social significance of the disease for the individual are described. The attributive dimension in the structure of attitudes towards healthy and chronically ill people is considered. The results are discussed in the context of intergroup differentiation.